-(t+2)=-3+23

Simple and best practice solution for -(t+2)=-3+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(t+2)=-3+23 equation:



-(t+2)=-3+23
We move all terms to the left:
-(t+2)-(-3+23)=0
We add all the numbers together, and all the variables
-(t+2)-20=0
We get rid of parentheses
-t-2-20=0
We add all the numbers together, and all the variables
-1t-22=0
We move all terms containing t to the left, all other terms to the right
-t=22
t=22/-1
t=-22

See similar equations:

| 2z+2∗2+3z∗2=114 | | -18d=-19d-20 | | 2(h−4)=4 | | M1=4x+7 | | 222-u=283 | | -9t=-10t+7 | | 9x+5=6x=3 | | 19=g/2+15 | | 2(p−4)=4 | | m+(-13)=-7 | | 2(3x+4)+3=4+3x | | 7n-16=14n+17 | | 12a-47=33-4a | | 6-1x=23 | | 8m+120=2m+160 | | 3x+4=6+x | | ∠B=4x+48 | | n/1/2=1/8 | | -61=8-1/3(12w+43)-w | | 3x-12=-8-2x | | 7x+8−9x=7x−28 | | -1-d=2+2d | | 22x-33=10x=10=5 | | x-1/2=3/2* | | 14+10z=9z | | 2+3n=8-3n | | 7(y+2)=3y-6 | | -8-13t=-11t-2 | | 3(4n+4)=1/2(6n+4) | | 12*x=72 | | -9=12-n | | 3u+8=4u |

Equations solver categories